Sensitivity of Fluconazole on Candida Species that Cause Onychomycosis at Haji Adam Malik Hospital Medan - Wardani, Meidina Kesuma; Mustika, Arzia (Green Publisher Indonesia, 2025)
Onychomycosis is an infection of the nail component caused by a fungal. Fungal groups that play a role are dermatophytes, non-dermatophytes, and candida. Fluconazole is a commonly used antifungal for onychomycosis caused by Candida spp. To determine the sensitivity of fluconazole on candida species that cause onychomycosis. This in vitro experimental study employed a consecutive sampling method and involved 30 patients presenting clinical features of onychomycosis. Each participant underwent anamnesis, physical and dermatological examinations, followed by nail specimen collection, which was sent to the Clinical Microbiology Laboratory. Initial examination was performed using a 20% KOH solution, followed by fungal culture and fluconazole sensitivity testing. Data analysis was conducted using the Kruskal–Wallis test. Ethical approval was obtained from the Research Ethics Committee of University of North Sumatra and H. Adam Malik Hospital. Candida onychomycosis was more common in women (80%), mostly aged 36–55 years (66.7%), and frequently found in janitors and assistants (40%). Negative KOH results occurred in 76.7% of cases. Candida albicans was the most prevalent species (53.3%), and 96.7% of isolates were sensitive to fluconazole. There were significant differences in fluconazole sensitivity based on culture results (p=0.039). There was found that fluconazole is sensitive to onychomycosis caused by candida species.